J.J. Abrams : interviews - Dunham, Brent (Conversations with filmmakers series., 2019)
"Jeffrey Jacob "J. J." Abrams (b. 1966) decided to be a filmmaker at the age of eight after his grandfather took him on the back-lot tour of Universal Studios. Throughout his career, Abrams has dedicated his life to storytelling and worked tirelessly to become one of the best-known and most-successful creators in Hollywood. The thirty interviews collected in this volume span Abrams's entire career, covering his many projects from television and film to video games and theater. The volume also includes a 1982 article about Abrams as a teen sensation whose short film High Voltage won the Audience Award at a local film festival and garnered the attention of Steven Spielberg. Beginning his career as a screenwriter on films like Regarding Henry and Armageddon, Abrams transitioned into a TV mogul with hit shows like Alias and Lost. Known for his imaginative work across several genres, from science fiction and horror to action and drama, Abrams's most successful films include Mission: Impossible III; Star Trek; and Star Wars: The Force Awakens, which went on to become the highest grossing film of all time in the United States. His production company, Bad Robot, has produced innovative genre projects like Cloverfield and Westworld. Abrams also cowrote a novel with Doug Dorst called S. and, most recently, he produced the Broadway run of The Play That Went Wrong. In conversations with major publications and independent blogs, Abrams discusses his long-standing collaborations with others in the field, explains his affinity for mystery, and describes his approach to creating films like those he gravitated to as a child, revealing that the award-winning director-writer-producer is a fan before he is a filmmaker."--Provided by publisher.